2013
DOI: 10.1016/s1734-1140(13)71031-4
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and VEGF in the pathogenesis of stress-induced affective diseases: An insight from experimental studies

Abstract: Stress is known to play an important role in etiology, development and progression of affective diseases. Especially, chronic stress, by initiating changes in the hypothalamic-pituitary-adrenal axis (HPA), neurotransmission and the immune system, acts as a trigger for affective diseases. It has been reported that the rise in the concentration of pro-inflammatory cytokines and persistent up-regulation of glucocorticoid expression in the brain and periphery increases the excitotoxic effect on CA3 pyramidal neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 95 publications
0
37
1
Order By: Relevance
“…BDNF protein and mRNA expression are down-regulated in postmortem hippocampus in MDD and suicide (Dwivedi et al, 2003; Duric et al, 2010). In addition, exposure to chronic stress or glucocorticoids decreases the expression of BDNF protein and mRNA in the rodent hippocampus (Duman and Aghajanian, 2012; Nowacka and Obuchowicz, 2013). Antidepressant-like effects of BDNF itself are well-documented, and they may involve direct effects of BDNF on astrocytes (Nowacka and Obuchowicz, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…BDNF protein and mRNA expression are down-regulated in postmortem hippocampus in MDD and suicide (Dwivedi et al, 2003; Duric et al, 2010). In addition, exposure to chronic stress or glucocorticoids decreases the expression of BDNF protein and mRNA in the rodent hippocampus (Duman and Aghajanian, 2012; Nowacka and Obuchowicz, 2013). Antidepressant-like effects of BDNF itself are well-documented, and they may involve direct effects of BDNF on astrocytes (Nowacka and Obuchowicz, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a decrease in VEGF levels in the hippocampus of rats in response to both chronic and acute stress, whereas other studies, including both rat and mouse studies, have found no change in the level of this growth factor 100 . The majority of studies report that VEGF increases cell proliferation through the activation of VEGF receptor 2 (also known as FLK1), which is expressed in neural progenitors and induces CREB signalling [101][102][103][104] .…”
Section: Neurotrophic Factorsmentioning
confidence: 95%
“…For example, VEGF has been proven to promote neurogenesis in the hippocampus (Fournier and Duman, 2012), provide neuroprotection (Feng et al, 2011), effect responses to stress (Nowacka and Obuchowicz, 2013), influence synaptic transmission (McCloskey et al, 2005), and protect neurons from oxidative stress (Hao and Rockwell, 2013). Furthermore, in one study conducted on a post-mortem brain of a patient with schizophrenia, the authors reported a significantly lower VEGF mRNA expression localized in the post-mortem dorsolateral prefrontal cortex (Fulzele and Pillai, 2009).…”
Section: Introductionmentioning
confidence: 99%